2020
DOI: 10.1073/pnas.2007472117
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of MAIT cell recognition by the AfricanSalmonellaTyphimurium ST313 pathovar that causes invasive disease

Abstract: Mucosal-associated invariant T (MAIT) cells are innate T lymphocytes activated by bacteria that produce vitamin B2 metabolites. Mouse models of infection have demonstrated a role for MAIT cells in antimicrobial defense. However, proposed protective roles of MAIT cells in human infections remain unproven and clinical conditions associated with selective absence of MAIT cells have not been identified. We report that typhoidal and nontyphoidal Salmonella enterica strains activate MAIT cells. However, S. Typhimuri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
(123 reference statements)
0
15
0
Order By: Relevance
“…Further, a recent study showed that Lineage 2 isolates of S . Typhimurium ST313 escape early immune recognition by MAIT cells (mucosal immune cells), via overexpression of the bacterial enzyme RibB 53 . Similar to ST313, our initial observations suggest that Salmonella 4,[5],12:i:- Lineages 2 and 3 may have also evolved specific immune evasion mechanisms to maintain the viability of host cells and confer a competitive advantage over Lineage 1 isolates and possibly other biphasic NTS.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent study showed that Lineage 2 isolates of S . Typhimurium ST313 escape early immune recognition by MAIT cells (mucosal immune cells), via overexpression of the bacterial enzyme RibB 53 . Similar to ST313, our initial observations suggest that Salmonella 4,[5],12:i:- Lineages 2 and 3 may have also evolved specific immune evasion mechanisms to maintain the viability of host cells and confer a competitive advantage over Lineage 1 isolates and possibly other biphasic NTS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antigen availability may differ across different isolates of the same pathogen, as shown for Steptococcus pneumoniae, resulting in differential MAIT cell activation (Hartmann et al, 2018;Kurioka et al, 2017). A novel mechanism of evasion from MAIT cell recognition has been reported for the African Salmonella typhimurium ST313 isolate that causes invasive disease (Preciado-Llanes et al, 2020). In this isolate, overexpression of ribB, encoding for a key enzyme in the riboflavin biosynthetic pathway, increases the overall amount of non-agonist metabolites such as riboflavin, flavin mononucleotide (FMN), flavin adenine dinucleotide (FAD), so that infected cells fail to effectively activate MAIT cells (Preciado-Llanes et al, 2020).…”
Section: Evasion Of Mr1-dependent Antigen Presentationmentioning
confidence: 99%
“…A novel mechanism of evasion from MAIT cell recognition has been reported for the African Salmonella typhimurium ST313 isolate that causes invasive disease (Preciado-Llanes et al, 2020). In this isolate, overexpression of ribB, encoding for a key enzyme in the riboflavin biosynthetic pathway, increases the overall amount of non-agonist metabolites such as riboflavin, flavin mononucleotide (FMN), flavin adenine dinucleotide (FAD), so that infected cells fail to effectively activate MAIT cells (Preciado-Llanes et al, 2020). Importantly, these results also suggest that weak MAIT cell agonists of the lumazine family (Corbett et al, 2014) do not accumulate at concentrations sufficient to elicit MAIT cell activation and are rapidly converted into non antigenic riboflavin, FMN, and FAD (Preciado-Llanes et al, 2020).…”
Section: Evasion Of Mr1-dependent Antigen Presentationmentioning
confidence: 99%
“…This adaptation results in hyper-dissemination of Salmonella via CD11b + CCR7 + migratory DCs (migDCs) through the lymphatics ( Carden et al, 2017 ). ST313 has evolved other mechanisms to promote invasive disease such as overexpression of ribB to avoid detection by Mucosal-associated Invariant T cells by reducing their activation ( Preciado-Llanes et al, 2020 ). SseI, a known immunogen that induces a potent and sustained CD4 + T cell response, inhibits the migration of infected DCs ( Kurtz et al, 2014 ; Carden et al, 2017 ).…”
Section: Adaptive Immune Responses To Intestinal Salmonellamentioning
confidence: 99%